Application of coaching model to promote the adult vaccine clinics - Saiprom, Kaitsuda; Chanmaung , Doungjun (Disease Control Journal, 2026)
The Department of Disease Control, Ministry of Public Health, developed an adult immunization program in 2016. This includes establishing guidelines and service models for adult vaccination clinics, which serve as service points with vaccines under the National Immunization Program. The goals of adult vaccine clinics are to provide comfortable and sustainable access to vaccination for target populations, under national standard, enhance immunity across all age groups. This study aimed to examine the support model for promoting adult vaccination clinics within Health Region 9 during the 2024 fiscal year. From December 7, 2023, to July 9, 2024. Office of Disease Prevention and Control, Region 9 Nakorn Ratchasima (ODPC 9) promoted and supported adult vaccination clinics in a total of 28 healthcare service units. This study used the GROW model (coaching approach) to enhance the implementation of adult vaccination clinics. There are 22 healthcare service units (78.57%; p<0.05) that has improved their operations according to the criteria of the Ministry of Public Health, with an average score at 13.29 from totally 16 points. The increasing of coverage vaccine in healthcare service units such as diphtheria-tetanus vaccine were 10 healthcare service units (35.71%; p=0.06) and influenza vaccine in pregnant group were 15 healthcare service units (53.57%; p=0.02). The results showed that the GROW model can be applied to enhance the implementation of adult vaccine clinic. To improve vaccine coverage and immunity in adults, the problems of immunization services in term of access to vaccine services and tracking of target population is recommended to be strengthened.